Study on historical commuter traffic pattern of Dhaka-Chittagong Highway (NH-1) of Bangladesh - Ullah, Mohammad Ahad; Nikraz, Hamid; Hoque, M. (2016)
Dhaka-Chittagong Highway, which is the main transportation artery for the economy of Bangladesh. Approximately 257 kilometers in length, the road links the country's two largest cities, Dhaka and Chittagong. The NH-1 is a top development priority and is the most demanding road in Bangladesh. Recent enormous congestion, long traffic queue and road accidents ascertains that the highway was built based on non-engineered way or else proper traffic study was not performed during the construction of that highways. Regrettably no extensive traffic studies have been completed on NH-1 by the Government of Bangladesh till now. However, an attempt is made through this research to establish daily, weekly and monthly traffic flow factors along NH-1. Usually traffic data collection and analysis follows varying trends and plays an important role in the evaluation and management of road network schemes. Traffic flow pattern is highly required for different purposes by different ministries and organizations in Bangladesh. The major areas for which this type of study is required are planning prioritization, project initiation, project design, planning maintenance, national transport statistics, road safety measures and traffic control. The daily, weekly and monthly traffic flow arrangements of Dhaka-Chittagong highway have been observed separately in this study. Some specific observation includes that Friday possess maximum traffic flow of 16.20% of weekly volume in NH-1 corridor, Sunday has the minimum traffic flow of 13.51% of the weekly volume and the average daily flow pattern sags on midweek. Likewise, there is a trend of increasing traffic in the first three weeks of a month and decreasing traffic in the last week of a month. It is also detected that the average maximum monthly flow percentage occurs more frequently on November and December. On the contrary, February carries minimum flow more frequently. © IAEME Publication.